Trend 2000 - 2012. Statistics Canada. CANSIM: Retail and Wholesale - Retail Sales by Type of Product | Country: Canada | Province: Northwest Territories | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Beer, Canadian products, Total sales, Value in dollars | Units: , 2000-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-176. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Retail and Wholesale - Retail Sales by Type of Product | Country: Canada | Province: Northwest Territories | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Beer, Canadian products, Total sales, Value in dollars | Units: , 2000-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-176. Dataset: Provides statistics on retail sales in Canada by type of product (commodity). Estimates of the distribution of the sales in retail outlets are broken down for more than 100 commodity groups. The retail industry is primarily engaged in selling consumer goods and related services to the general public. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Retail Sales, Consumer Products, Retail Trade